In Search of Territorial Cohesion: An Elusive and Imagined Notion - Rob Atkinson; Carolina Pacchi (Social Inclusion, 2020)
Territorial cohesion has figured in the lexicon of the European Union for some years. However, there has never been a clear definition of the notion, not even after its inclusion in the Lisbon Treaty. Moreover, within the European Union Cohesion Reports and, more generally, within European Union documents, along with the other two dimensions of cohesion (economic and social) it has been treated separately without any serious attempts to reconcile them and develop a coherent interpretation of cohesion—the result being the creation of a contested and ill-defined understanding of territorial cohesion and its relationship to the other two dimensions of Cohesion Policy. Given that the approach advocated by Directorate-General for Regional and Urban Policy aims to embed the different dimensions and how they interact in specific spatial configurations (created by the confluence of a range of different ‘flows’ that can create multiple overlapping assemblages with ‘fuzzy’ boundaries), this raises important questions about how we understand these relationships. Moreover, the policy discourses in which each dimension of cohesion is situated create their own frameworks that are conducive to developing the conditions, including appropriate policy strategies, to supporting these individual cohesion formations. The rather arbitrary separation of these approaches in ‘official discourse’ impedes addressing cohesion in a coherent and integrated manner. Thus, after reviewing the relevant key policy literature, the article will seek to consider how territorial cohesion relates to the other two dimensions of cohesion taking into account the role of the place-based approach. However, it is argued that the search for territorial (social and economic) cohesion has been subordinated to neoliberal notions such as competitiveness and economic growth.